2012
DOI: 10.1111/j.1479-8298.2012.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoreception in decapitated larvae of silkworm Bombyx mori

Abstract: To investigate the photoreception that controls daily oscillations at the periphery in insects, we decapitated larvae of the silkworm Bombyx mori (Lepidoptera: Bombycidae) by ligature, and observed rhythms in their peripheral tissues under several light conditions. We measured the mRNA expression of period (per) and timeless (tim), which are homologues of Drosophila clock genes that function in the core oscillator of the circadian clock system. The expression of both per and tim significantly changed in the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…Expression peaks occurred in the early scotophase, and expression levels were low in the photophase. Similar expression trends were reported in the adult brain and larval midgut of B. mori (Iwai et al, 2006; Nobata et al, 2012). Tao et al (2017) showed in the embryo of this species that the expression peak of per also resides in the earlier scotophase but that of tim occurred in the later scotophase.…”
Section: Discussionsupporting
confidence: 81%
“…Expression peaks occurred in the early scotophase, and expression levels were low in the photophase. Similar expression trends were reported in the adult brain and larval midgut of B. mori (Iwai et al, 2006; Nobata et al, 2012). Tao et al (2017) showed in the embryo of this species that the expression peak of per also resides in the earlier scotophase but that of tim occurred in the later scotophase.…”
Section: Discussionsupporting
confidence: 81%
“…Although extensive and standardized studies have not always been performed, several tissues have been shown to express multiple clock factors during larval development in species such as B. mori , S. litura , and S. littoralis . Specifically, last (5th) instar larvae of B. mori actively transcribe the clock genes Bm tim , Bm per , Bm Clk , and Bm Bmal1 in the head, midgut, fat body, and silk glands ( Markova et al, 2003 ; Iwai et al, 2006 ; Xu et al, 2011 ; Nobata et al, 2012 ). In the midgut, a significant cycling expression of Bm tim was demonstrated in both LD and DD, while Bm per mRNA levels tended to be higher during the night compared to the day ( Nobata et al, 2012 ).…”
Section: The Circadian System In Lepidopteramentioning
confidence: 99%
“…Specifically, last (5th) instar larvae of B. mori actively transcribe the clock genes Bm tim , Bm per , Bm Clk , and Bm Bmal1 in the head, midgut, fat body, and silk glands ( Markova et al, 2003 ; Iwai et al, 2006 ; Xu et al, 2011 ; Nobata et al, 2012 ). In the midgut, a significant cycling expression of Bm tim was demonstrated in both LD and DD, while Bm per mRNA levels tended to be higher during the night compared to the day ( Nobata et al, 2012 ). Among the multiple cell types composing the silkworm midgut, BmPER staining was limited to goblet cells, known for their role in the active transport of potassium from hemolymph into the gut lumen and in the release of digestive enzymes ( Daimon et al, 2008 ; Park et al, 2014 ).…”
Section: The Circadian System In Lepidopteramentioning
confidence: 99%